An exploration of adolescent stalking: from understanding perpetration to its harmful effects upon its victims - Mckechnie, Amy (2019)
This thesis broadly explores multiple aspects of adolescent stalking, including perpetration and victimisation. A range of explorative methods are used to achieve this, including an empirical research paper, a single case study, a critique of a forensic risk assessment (SAVRY) used in the case study, and a systematic review. Following an introduction in Chapter One, Chapter Two describes a mixed methods research study investigating male adolescents’ perceptions of low-level stalking and the behaviours and possible motives of perpetrators engaging in obsessive relational intrusive behaviour. Comparisons are made between adolescents residing in a forensic medium secure unit and young people attending a community college. Results are discussed, limitations are highlighted, and future recommendations are made. Chapter Three discusses the forensic assessment process of a male adolescent who has a history of engaging in intrusive behaviours directed towards his ex-partner. This single case study examines the young person’s risk of future violent recidivism, which is assessed through utilising a widely-used youth forensic risk assessment tool. A theory-driven formulation attempts to explain his intrusive behaviours from a psychological perspective before finally providing future treatment recommendations. Chapter Four critically appraises an adolescent forensic risk assessment tool, the Structured Assessment of Violence Risk in Youth (SAVRY; Borum, Bartel & Forth, 2002), the assessment measure used in Chapter Three. Chapter Five reviews the stalking literature, specifically examining how stalking impacts upon victims’ lives. Fourteen full references were systematically identified that met the review’s inclusion criteria. Studies indicate that victims of both direct and indirect stalking suffer severe consequences in their lives as a result. Future longitudinal studies, controlling for confounding biases, are necessary for achieving a richer understanding of the impact that stalking can have on victims. Finally, Chapter Six discusses the implications of this thesis and offers recommendations for future research.